Management Implications: Repurchase Decisions in the Retail Technology Supply Chain in the Retail Industry in Digital Retail Companies - Irnaldi, Devi; Jimmy, So Yohanes; Hasan, Djohan Gunawan (International Journal Labs, 2023)
This study aims to find out how digital retail companies retain their customers by being active as registered partners who continue to make repurchases. Understanding partner’s positive perceptions is key in improving repurchase decisions. Marketing Strategy, Service Quality and situational factors are studied to understand the strengthening of these positive perceptions. Attitude Towards Norm is known as one of the predictors in influencing purchasing decisions so that the relationship between these variables is also studied in this study. This research method is quantitative. Data obtained from an online questionnaire of 384 respondents. Descriptive analysis was conducted to determine the demographic background of the respondents. Associative analysis was carried out to identify the relationship between Marketing Activities, Service Quality, Attitude Towards Norm, Social Influence and Repurchasing Decision. The results show that all the effects of exogenous variables are found to be significant, except that Service Quality does not directly have a significant effect on Repurchase Decision.